Synergic mitigation of saline-alkaline stress in wheat plant by silicon and Enterobacter sp. FN0603 - Xu, Fangfang; Liang, Yungang; Wang, Xiaobing; Guo, Yuze; Tang, Kai; Feng, Fuying (Frontiers in Microbiology, 2023)
Although microorganisms and silicon are well documented as factors that mitigate salt stress, their effect mitigating saline-alkaline stress in plants remains unknown. In this study, wheat plant seeds were treated with silicon, Enterobacter sp. FN0603 alone and in combination of both. Wheat seeds were soaked in silicon and bacterial solutions and sown in pots containing artificial saline-alkaline soils to compare the effects among all treatments. The results showed that the treatments with silicon and FN0603 alone significantly changed plant morphology, enhanced the rhizosphere soil nutrient content and enzyme activities, improved some important antioxidant enzyme activities (e.g., superoxide dismutase) and the contents of small molecules (e.g., proline) that affected osmotic conditions in the top second leaves. However, treatment with silicon and FN0603 in combination significantly further increased these stress tolerance indexes and eventually promoted the plant growth dramatically compared to the treatments with silicon or FN0603 alone (P < 0.01), indicating a synergic plant growth-promoting effect. High relative abundance of strain FN0603 was detected in the treated plants roots, and silicon further improved the colonization of FN0603 in stressed wheat roots. Strain FN0603 particularly when present in combination with silicon changed the root endophytic bacterial and fungal communities rather than the rhizosphere communities. Bipartite network analysis, variation partitioning analysis and structure equation model further showed that strain FN0603 indirectly shaped root endophytic bacterial and fungal communities and improved plant physiology, rhizosphere soil properties and plant growth through significantly and positively directing FN0603-specific biomarkers (P < 0.05). This synergetic effect of silicon and plant growth-promoting microorganism in the mitigation of saline-alkaline stress in plants via shaping root endophyte community may provide a promising approach for sustainable agriculture in saline-alkaline soils.